# Tangent line of a convex function

Let $V : \mathbb{R}^n \rightarrow \mathbb{R}$ be (strictly) convex and continuously differentiable on $\mathbb{R}^n$. Show that for any $y \in \mathbb{R}^n$ and any $x \in \mathbb{R}^n$ $$V(y) \geq V(x) + \nabla V(x)^\top(y-x)$$ For $n=1$ this implies that for any $x \in \mathbb{R}$ and for any $y \in \mathbb{R}$, $V(y)$ lies above the tangent line to $V$ at $x$.

• What is your definition of convexity? – J.R. Feb 8 '14 at 18:26
• You can reduce this to the onedimensional case by considering only the line through $x$ and $y$. Notice that $\nabla V(x)^T (y-x)$ is a directional derivative. – Christoph Feb 8 '14 at 18:27

$\newcommand\R{\mathbb R} \newcommand\x{\mathbf x} \newcommand\y{\mathbf y}$Let $\gamma\colon\R\to\R^n$ be the curve defined by $t\mapsto \x+t(\y-\x)$, which is a straight line through $\gamma(0)=\x$ and $\gamma(1)=\y$. Further define $\widetilde V=V\circ \gamma:\R\to\R$.

Since $V\colon\R^n\to\R$ is differentiable, \begin{align} \nabla V(\x)\cdot (\y-\x) &= \lim_{h\to 0} \frac{V(\x+h(\y-\x))-V(\x)}{h} \\&= \lim_{h\to 0} \frac{V(\gamma(h))-V(\gamma(0))}{h} = \widetilde V'(0). \end{align}

Thus, your inequality can be expressed as $$\widetilde V(1) \ge \widetilde V(0) + \widetilde V'(0).$$

It is easy to check that $\widetilde V$ is convex given that $V$ is convex.

After this, we have reduced everything to the claim foir $n=1$, $x=0$ and $y=1$.

Since $\widetilde V$ is convex, for all $t\in(0,1)$ we have $$\widetilde V(t) \le (1-t) \widetilde V(0) + t\widetilde V(1)$$ which is equivalent to $$\widetilde V(0) + \frac{\widetilde V(t)-\widetilde V(0)}{t} \le \widetilde V(1).$$ Letting $t\to 0$ gives the desired inequality.

This is true for any differentiable convex function. Let $f(t) = V(x + t (y-x))$ for $t \in [0,1]$.

First we establish an essentially equivalent (and fundamental) result that applies to all finite-valued convex functions: Suppose $x<y$, and let $R(x,y) = { f(x)-f(y) \over x-y }$. Then if $r < s<t$, we have $R(s,r) \le R(t,s)$.

To see this, note that if $s = \lambda t + (1-\lambda) r$, then $f(s) \le \lambda f(t) + (1-\lambda) f(r)$, or equivalently, $0 \le \lambda (f(t)-f(s)) + (1-\lambda) (f(r)-f(s))$. Since $\lambda = {s-r \over t-r}$ and $1-\lambda = { t-s \over t-r}$, substituting gives the result.

Now let $s = r+h$, where $0 < h < t-r$, then taking limits as $h \downarrow 0$ shows that $f'(r) \le R(t,r)$, or $f(t) \ge f(r) + f'(r) (t-r)$.

Choosing $t=1, r=0$ and noting that $f'(0) = \langle \nabla V(x), y-x \rangle$ yields the desired result.